Organizational culture as a factor of innovative readiness of personnel of informal educational establishments - J. Lukomskaya (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
This paper considers the importance of educational institutions for the further development of the world and underlines the particular importance of the cultivation of creative personality. The author admits that only creative personalities could make original decisions, look for unconventional solutions to problems and change the reality. It is underlined that the current situation requires for crossovering to the so-called advanced pedagogy as the way of studying new type of thinking. There are two main types of educational systems in Ukraine. They are school education and out of school or extracurricular education. The author suggests considering world’s most creative type of education which is non-formal education. Non-formal educational establishmentsare the most atypical and unusual for Ukrainian educational realities and are not presented at the national level yet. The author examines the organizational culture of the educational establishments and their connection with the innovative readiness of personnel. The study of organizational culture, in author’s opinion, is the key, because, the values of organizations positively affect the results. Besides, there is a 5-component model of innovation readiness which includes cognitive, motivational, creative, practical and collective components while mathematical and statistical calculations confirm the hypothesis of this article. In conclusion the author provides the results of the study which claim that the lower the level of formalization of organizational culture, the higher will be the innovation readiness of personnel. The prospects for future research are also provided and outlined.